500 anni fa: l'Europa moderna: Ignazio, Lutero, Carlo V, Magellano - Pani, Giancarlo (La civiltà cattolica, 2021)
The sixteenth century marks the beginning of the Modern Age, which was when contemporaneously a number of historically new events took place. These include, the invention of printing, geographical discoveries, gunpowder, a new way of marking time (clocks), of experiencing it, and the relationship with money (“time is money!”), the development of banking, insurance, but above all a new awareness of man’s identity and dignity. Some particular events at the very beginning of the century document this. For example, the Diet of Worms in 1521 and the way in which Charles V planned the unity of the Empire, that is, of Europe; the Reformation and Ignatius of Loyola; Magellan’s circumnavigation of the world; the emergence of new relationships between citizens and the prince, between the faithful and the Church. Collectively, these bring to mind the “Europe of the spirit” on which Cardinal Carlo Maria Martini reflected.